Psychometric properties of the Malay version of the Medical Outcomes Study Social Support Survey (MOS-SSS) in a sample of patients with HIV. Issue 1 (2nd January 2017) - Saddki, Norkhafizah; Sulaiman, Zaharah; Abdullah, Sarimah; Zakaria, Norzila; Mohamad, Norsarwany; Ab Razak, Asrenee; Zainan Abidin, Zarina
ABSTRACT: We determined the validity and reliability of the Malay translated MOS-SSS. A sample of 120 HIV patients participated in this study. Forty patients completed the self-administered 19-item questionnaire again after 1–2 weeks to test its reliability. Exploratory factor analysis resulted in four-factor solution which was consistent with the original subscales. All items had primary factor loadings > 0.40 without cross-loading. The Cronbach's alpha values for the subscales ranged from 0.87–0.95. Intraclass correlation coefficient for the overall scale was 0.88. In conclusion, the Malay version of the MOS-SSS is valid and reliable for measuring perceived functional social support in patients with HIV.